Needs Analysis to Develop Linear Motion E-Student Worksheet Based on Inquiry Learning Model and Local Wisdom to Improve Student’s Critical Thinking Skills - Farah Azzahra Ramadhina; Hidayati Hidayati; Desnita Desnita; Leni Aziyus Fitri (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Twenty-first-century physics learning requires innovative teaching materials to improve students' critical thinking skills. Currently, physics instruction still relies on conventional printed textbooks that lack variation. This study aims to analyze the need for developing an E-Student Worksheet based on Inquiry learning and oriented to local wisdom in linear motion kinematics material to enhance high school students' critical thinking skills. The study used a descriptive approach with a preliminary study research type. The subjects consisted of one physics teacher and 34 tenth-grade students at SMA Negeri 9 Padang. Data was obtained and triangulated through a structured combination of observations, interviews, questionnaires, and critical thinking skills tests. The results showed that students' critical thinking skills were still relatively low, with an average score of 38.4%, especially in the analysis indicator. In addition, students strongly need interactive digital teaching materials that systematically support contextual, inquiry-based learning. Therefore, developing an E-Student Worksheet based on Inquiry learning oriented to local wisdom is highly important to support more active and meaningful physics learning.